Faktor Lingkungan Dan Perilaku Masyarakat yang Berhubungan dengan Kejadian Filariasis di Kota Semarang - Kartika Dian Pertiwi; Nurjazuli Nurjazuli (Pro Health Jurnal Ilmiah Kesehatan, 2019)
Since 2011 until 2016 filariasis incidence in Semarang City increases. Until 2016 has reported 28 filariasis cases. Filariasis control program has not been implemented, and there is no information about the determinants of filariasis transmission in relation to vector and humans in Semarang City. This study aimed to determine relation between environmental factors and behavioral factors with filariasis incidence, and to know the potential transmission of filariasis in Semarang City.data was collected through labocatory examination, observation, and interviews. The study was an analytic observational study using case control design, which consisted of 21 cases, and 21 controls. Data were analyzed using chi-square and continued with logistic regression used conditional backward method. From the surgery of 182 mosquitos, found no positive for mosquitos larvae of filaria. Species indentification were found Culex quinquefasciatus, Aedes aegypti, and Armigeres sp. Variables had assosiated with filariasis incidence in Semarang are breeding place (p-value= 0,017, OR = 8,636), resting place (p-value= 0,022, OR = 6,6), knowledge (p-value= 0,026, OR = 5,667), attitude (p-value= 0,029, OR = 5,2). Examination Â of blood finger sample not found microfilaria in blood. The most potent variables that influent filariasis incidence in Semarang City are knowledge, mosquito breeding place, and mosquito resting place.